Акумуляція енергії Землі та її використання у побутових потребах - Проніна, В. І. (ХНУРЕ, 2021)
This work presents the idea of using the thermal energy of the earth as a renewable energy that can be applied for space heating. This idea is realized as the connection of a heat exchanger, a conductor of thermal energy and a room, which must be heated or maintain a constant temperature when there is no possibility for humans to control the heating process. The basis for the physical justification is the inverse Carnot cycle and the physical process of heat absorption-emission during the phase transition of substances. This mechanism has already been implemented on several residential properties
Keywords: акумуляція енергії Землі